The impact of livelihood diversification as a climate change adaptation strategy on poverty level of pastoral households in southeastern and southern Ethiopia - Baro Beyene; Mesfin Tilahun; Mebratu Alemu (Cogent Social Sciences, 2023)
AbstractThe purpose of this study was, therefore, to examine the determinants of poverty depth in pastoral households, and the impact of adopting livelihood diversification on the poverty level of households in the Arero district of Borena Zone and Rayitu district of Bale Zone, Ethiopia. A multistage sampling technique was used, and 396 households were selected from the Arero and Rayitu Districts. The cost of basic needs (CBN) approach was used to determine the study areas. Accordingly, the absolute poverty line was determined to be 10,881.26 Birr per adult per annum. Based on the poverty line, 34.6 % of the sample households were in the poor category. The Foster-Greer-Thorbecke index results indicated that the poverty incidence, poverty gap, and poverty severity were 34.6, 9.28, and 3.62, respectively. Two econometric models were used for the analysis, namely the Tobit and Multinomial Endogenous Switching models. The results of the Tobit logistic regression revealed that the age of the household head, household size, and distance to the nearest market significantly increased the poverty level of the pastoral households. However, livestock size as measured by tropical livestock unit and frequency of extension contact significantly decreased the poverty depth of pastoral households. On the other hand, the output of the multinomial endogenous switching regression model showed that the joint adoption of non-farm activities and crop production had a decreasing and significant impact on the poverty level of pastoral households. Therefore, policies that promote livelihood diversification of pastoral communities are critical to lowering the poverty level of pastoral households in semi-arid areas.